Visual Suggestions via Photos With Hunting Trophies (Validation of Cultural Indexes Through Photographic Images in the Mass Communication) - Zahariev, Ivan (Media and Language, 2021)
The aim of this research is to explore the impact of photographs of hunters with killed animals that are published in the press or the social media. The object of the research are images of hunters, who having finished the hunting, pose with their trophies. All of the images are in „memory photograph“ style and are very typical – a man (or a group of men) with hunting weapons that are in structural unity with a body (or many bodies) of killed animals. The research aims to show the coded suggestions of the pictures that impact the mass public. The main hypothesis is that the hunting photographs are actually cultural self-description influenced by national symbols, rituals and values. The method of the research is the content analysis of the photographic images through decoding their meaning. The models used for this purpose are that of Harold Lasswell and Friedemann Schultz von Thun. The result of the research should draw conclusions about the effects of the techniques for coding and decoding of non-verbal suggestions in the mass media for the purpose of the collective cultural programming and about the role that the people attribute to the natural surrounding, according to the researches of Geert Hofstede and Fons Trompenaars. As a result of the mass publications of photographs of hunters with trophies, a validation of the cultural indexes is fulfilled. The conclusions about the functional purpose of the images of hunters with trophies can be resumed as an aimed impact that provokes reactions which are useful for the manipulator.